An 8-week Controlled Feeding Trial Based on the 2010 Dietary Guidelines for Americans Has Minimal Effect on the Fecal Microbiota in Overweight and Obese Women (FS11-08-19). (13th June 2019) - Piccolo, Brian; Krishnan, Sridevi; Shankar, Kartik; Chintapalli, Sree; Ono-Moore, Kikumi; Adams, Sean; Keim, Nancy
Abstract: Objectives: To determine whether a high quality diet based on the 2010 Dietary Guidelines of America (DGA) alters the composition of the fecal microbiome in individuals at risk for cardiometabolic disease, compared to a diet based on a typical American diet (TAD). Methods: A total of 52 overweight and obese women were enrolled in a randomized, double-blind, controlled feeding trial. Women were randomly assigned to the DGA or TAD group ( n  = 28 DGA and 24 TAD). Diets matched each participant's estimated energy requirement and subjects remained weight-stable. The DGA diet was based on the 2010 DGA food-group recommendations, whereas the TAD diet was based on the average adult intake patterns from the NHANES 2009–2010 survey. Participants provided a stool sample 1-week prior to intervention (W0), within the second week of diet intervention (W2), and at the final week of intervention (W8). Microbial profiles were assessed using 16S rRNA amplicon sequencing and expressed as median % relative abundance. Data analyses were performed using standardized pipelines (QIIME 1.9 and R packages). False Discovery Rate (FDR) was set at 0.2. Results: No differences were found in α- and β-diversity indices at the operational taxomonic unit (OTU) level by diet assignment at W0, and no taxa were differentially abundant at FDR < 0.2. Similarly, α- and β-diversity indices (OTU level) were not altered by diet within W2 or W8. A single OTU within the Ruminococcus genera was higher in TAD at both W2 (TAD = 0.014%; DGA = 0.00%) and W8 (TAD = 0.017%; DGA = 0.00%; FDR < 0.05), and the Adlercreutzia genera from the Actinobacteria phyla was also higher in TAD at both W2 (TAD = 0.027%; DGA = 0.001%) and W8 (TAD = 0.022%; DGA = 0.002%). No within-diet differences between W0 and W2, and W0 and W8 were observed in any α- and β-diversity indices tested. When adjusting for W0 relative abundances, 10 OTUs were altered by diet at W2 and 39 OTUs were altered at W8. Conclusions: A weight-maintaining diet based on the 2010 DGA minimally differed in the fecal microbiota compared to a weight-maintaining typical American diet. Results herein suggests differences in food-based dietary patterns does not have a large effect on the composition of the fecal microbiota in humans. Funding Sources: Supported by National Dairy Council; Campbell Soup Co.; USDA-ARS Projects 2032-51530-022-00D and 6026-51000-010-05S.